COMPARISON OF LDR TO HDR IN TREATMENT OF CERVICAL CANCER. - TANGKARATT, SAIPIN (The ASEAN Journal of Radiology, 2023)
Objective; To compare the treatment results between LDR and HDR in FIGO stage IIB cervical cancer, in terms of disease survival and late normal tissues complications. Materials and methods; From Jan 1997 to Dec 1998, Prospective non-randomized study was conducted. About 161 patients with pathological diagnosis of FIGO stage IIB cervical cancer were included in the study. All patients were treated with combination of external beam radiation and brachytherapy. The patients were divided into 2 groups for difference brachytherapy protocols. The first group of patients was treated with 1-2 fractions of LDR, and the other group of patients was treated with 4-5 fractions of HDR. Total tumor dose to point A was 80-85 Gy. Results; All of 161 patients had complete radiation treatment as planned. Ninety patients entered in LDR protocal, and 71 patients entered in HDR protocal. The age of patients with LDR and HDR ranged from 29-82, and 29-80 years, respectively. The mean age was 45 years in both groups. The common subtype of both groups was squamous cell carcinoma, for LDR and HDR, accounted about 86% and 77%, respectively. The evaluable patients for LDR and HDR were 82 and 66, respectively. Three year survival of patients treated with LDR and HDR were 63.4% and 68% respectively. Fourteen of 52 responders patients (26.9%) with LDR had grade I proctitis, and 4 of 52 patients (7.7%) had grade I cystitis. About 6 of 45 responders patients with HDL had grade I proctitis, 1 of 45 patients had grade II proctitis, and 1 of 45 patients (2.2%) had cystitis. Conclusion; The study has shown the comparable results with a slightly better survival of HDR than LDR (68.2% VS 63.4%) without significant difference (p = 0.544). About late normal tissue complications, the LDR showed more than HDR for proctitis and cystitis (26.9% VS 15.6% and 7.7% VS 2.2%), respectively. (P = 0.062)